Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4084/mjhid.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

Beta Thalassemia Major in a Developing Country: Epidemiological, Clinical and Evolutionary Aspect

Abstract: Beta-thalassemia major (TM) remains to be one of the major health problems particularly in developing countries. Tunisia is a part of the Mediterranean countries mostly affected by this disease which is highly concentrated in small towns in families with low-income earners. The main objectives of this study are to provide a description of the demographic, clinical features and transfusion-related complications in patients with TM living in Tunisia. A standardized questionnaire was sent to clinicians throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
8
21
0
3
Order By: Relevance
“…About one-third (33%) of the cases were in the age group 7-10 years, followed by the age group 3-6 years. This result is in agreement with Bejaoui and Guirat reporting a median age of 10.7 years among thalassemic patients in Tunisia (35,38). In contrast to these results, in 2016, lower mean age of 3.7 years was reported in a similar study carried out in India.…”
Section: Monhal Et Al (2012) (22) Andsupporting
confidence: 91%
See 1 more Smart Citation
“…About one-third (33%) of the cases were in the age group 7-10 years, followed by the age group 3-6 years. This result is in agreement with Bejaoui and Guirat reporting a median age of 10.7 years among thalassemic patients in Tunisia (35,38). In contrast to these results, in 2016, lower mean age of 3.7 years was reported in a similar study carried out in India.…”
Section: Monhal Et Al (2012) (22) Andsupporting
confidence: 91%
“…Most importantly, our results show a highly increased frequency of close family members' marriages, most often cousins, in patients with HHD (78.24%) as compared with the expected consanguinity rate of 45.8%. One study, conducted in Tunisia, reported a consanguinity rate of 75.3% among the patients' parents (38). Another study reported that 40.6% of β-thal patients occurred in the offspring of first-cousin marriages (31).…”
Section: Monhal Et Al (2012) (22) Andmentioning
confidence: 99%
“…Mokhtar and associates [53] reported the presence of cardiovascular morbidities in 41.3% of β-thalassemia patients with cardiomyopathy being the most frequent (6.9%), followed by arrhythmia (1.6%) and PH (0.4%). Another study done by Bejaoui and Guirat [54] showed that cardiac disorders occurred in 19.8% of the studied β-TM patients with higher incidence of PH (12.5%) and heart failure (39%) being the major leading cause of death.…”
Section: Discussionmentioning
confidence: 87%
“…Thalassemia minor. 12 In thalassemia due to lack of total or partial production of α or β or globin results serious effects on their bodies, 2,3,9,11,13-16 Beta thalassemia is also responsible of causing various manifestations and complications, resulting multisystem complications due to chronic anemia, iron overload, adverse effects of chelation, and infection due to transfusion. Thus, just a simple hemolytic disease 'anemia' change to a chronic disease with involving various organs with various degree of deformities.…”
Section: Introductionmentioning
confidence: 99%